Delayed Interval Delivery in Triplet Pregnancy: A Case Report and Literature Review - Karalök, Hakan; Karalök, Ebru; Küpelioğlu, Latif; Ekin, Murat; Savan, Kadir (Gynecology Obstetrics & Reproductive Medicine, 2008)
We report a case of triplet gestation delivered at 22 weeks with an interval of 48 days. We performed immediately a McDonald’s cerclage after the first triplet’s delivery and used intravenous beta-mimetic and broad-spectrum antibiotics for 14 days. In the literature whereas delaying the delivery of remaining fetuses improves their prognosis, there is no consensus about optimal management for these patients.